Accurate detection of KRAS, NRAS and BRAF mutations in metastatic colorectal cancers by bridged nucleic acid-clamp real-time PCR - Yuki Nagakubo; Yosuke Hirotsu; Kenji Amemiya; Toshio Oyama; Hitoshi Mochizuki; Masao Omata (BMC, 2019)
Abstract Background Patients with metastatic colorectal cancer can benefit from anti-EGFR therapy, such as cetuximab and panitumumab. However, colorectal cancers harboring constitutive activating mutations in KRAS, NRAS and BRAF genes are not responsive to anti-EGFR therapy. To select patients for appropriate treatment, genetic testing of these three genes is routinely performed. Methods We applied bridged nucleic acid-clamp real-time PCR (BNA-clamp PCR) to detect somatic hotspot mutations in KRAS, NRAS and BRAF. PCR products from BNA-clamp PCR were subsequently analyzed Sanger sequencing. We then compared results with those from the PCR-reverse sequence-specific oligonucleotide probe (PCR-rSSO) method, which has been used as in vitro diagnostic test in Japan. To validate the mutation status, we also performed next generation sequencing using all samples. Results In 50 formalin-fixed paraffin-embedded tissues, KRAS mutations were detected at frequencies of 50% (25/50) and 52% (26/50) by PCR-rSSO and BNA-clamp PCR with Sanger sequencing, respectively, and NRAS mutations were detected at 12% (6/50) and 12% (6/50) by PCR-rSSO and BNA-clamp PCR with Sanger sequencing, respectively. The concordance rate for detection of KRAS and NRAS mutations between the two was 94% (47/50). However, there were three discordant results. We validated these three discordant and 47 concordant results by next generation sequencing. All mutations identified by BNA-clamp PCR with Sanger sequencing were also identified by next generation sequencing. BNA-clamp PCR detected BRAF mutations in 6% (3/50) of tumor samples. Conclusions Our results indicate that BNA-clamp PCR with Sanger sequencing detects somatic mutations in KRAS, NRAS and BRAF with high accuracy.